Trade and economic performance: does Africa’s fragmentation matter? - Collier, P; Venables, T (2008)
The population of South Asia lives almost entirely in one mega-country or two large ones. In contrast, the rather smaller population of sub-Saharan Africa is spread across some fifty countries. Does this political fragmentation have economic consequences? We suggest that both private economic activity and the provision of public goods benefit from powerful scale economies that confer advantages on the South Asian model. Paradoxically, although as a result Africa has a greater need than other regions for supra-national power structures, it has far less made less progress towards regional unity.